Potential Development of Tourist Village in Bali (International Journal of Psychosocial Rehabilitation, 2020)
This study aims at finding out (1) how the beginning of the Tenganan Pegringsingan Village grew into a tourist village, (2) to understand the potential of Tenganan Pegringsingan as a tourist village, and (3) the strategy of developing Tenganan Pegringsingan tourist village in Karangasem Regency, Bali Province. The theories used in this research were the hegemony theory and the power/knowledge theory. SWOT analysis was also used to formulate a strategy for developing tourism in the village in the future. The findings of this study indicate that the establishment of Tenganan Pegringsingan Tourist Village started with the issuance of the Karangasem Regent's Decree Number 658 in 2014. Seen from the potential of “4H-based tourism” owned by Tenganan Pegringsingan Village, there are only three elements, namely: (1) the habitat, consisting of Ombo and agrotourism tourist attractions; (2) handicrafts: Ate handicrafts, Prasi handicrafts, and Gringsing fabric; and (3) heritage, Mekare-kare attractions. The strategies that need to be carried out in developing this village were (1) utilizing the potential of tourism based on local wisdom, (2) exploring new potential tourism sources, (3) increasing tourism-supporting infrastructure and facilities, (4) holding various soft skills training, (5) holding tourism events such as the Tenganan Village festival, (6) cooperating with all tourism stakeholders, (7) cooperating with travel agents, (8) developing a new image of village tourism, (9) collaborating with the government, and (10) creating an online marketing team.